The international business environment: Text and cases - Sundaram, Anant K.; Black, J. Stewart (New Delhi: Pearson, 2015)
The International Business Environment is written with the aim to provide students with the necessary tools to analyse systematically the different facets of international business environment and how they affect an organization. The text focusses on five aspects of the cross border environment$1 (Bexchange rates and international capital markets, trading patterns and regimes, regulatory content, and political context. Theories, models, and insights have been integrated from a variety of disciplines and functional areas, while emphasizing managerial relevance and providing a general management focus to issues confronting the multinational enterprises (MNEs).s
Keywords: International Business Management; International Business Environment